Hyposidra talaca Walker (Geometridae: Lepidoptera) a New Pest (Defoliator) Recorded for Meyna spinosa Roxb. Ex Link from Assam, India - Saikia, Ankur Jyoti; Parkash, Vipin (Indian Forester, 2017)
No Abstract.